Integrating the Indonesian Competition Law and Renewable Energy Policy: Challenges and Strategies Towards Sustainability - Anna Maria Tri Anggraini; Ahmad Sabirin; Arif Wicaksana; Sharda Abrianti; Jimi Rambo Arranchado (Faculty of Law, Universitas Sebelas Maret, 2026)
The Indonesia's switch to renewable energy is crucial to combating climate change, meeting international decarbonisation goals, and ensuring energy security. However, institutional and regulatory barriers, especially under competition law, hinder renewable energy development. This paper examines whether Indonesia's competition law framework supports renewable energy development and proposes legal reform to balance market regulation and sustainability. The study analyses competition regulation and energy and regulatory development in the EU and China utilising normative legal research methods: statutory, conceptual, and comparison. The results show that Law Number 5 of 1999 still prioritises economic efficiency and market structure over sustainability. Renewable energy investment and innovation are hindered by market entry barriers, restricted infrastructural access, highly concentrated market structures, and state-owned energy businesses. A comparative analysis demonstrates that competition legislation can help energy transition when environmental and sustainability benefits are included. Therefore, this study recommends revising Article 51 of Law Number 5 of 1999, integrating sustainability criteria into competition analysis, providing fair access to energy infrastructure, and harmonising competition, energy, and environmental laws to create a more competitive, innovative, and sustainable renewable energy ecosystem in Indonesia.